X-3-1=5

Simple and best practice solution for X-3-1=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-3-1=5 equation:


Simplifying
X + -3 + -1 = 5

Reorder the terms:
-3 + -1 + X = 5

Combine like terms: -3 + -1 = -4
-4 + X = 5

Solving
-4 + X = 5

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + X = 5 + 4

Combine like terms: -4 + 4 = 0
0 + X = 5 + 4
X = 5 + 4

Combine like terms: 5 + 4 = 9
X = 9

Simplifying
X = 9

See similar equations:

| X^2-x+304=0 | | x/--6 | | 145/170 | | -8g+2g+g=-40 | | log(base)2(2^x/3)=log(base)2(80) | | 3x^2+6=9 | | 7r-12+17r+41= | | 2x+4x=5x+4 | | 6/7(-21t)= | | 3x-4.6=0.5x+26 | | 3(x-1)-2(x-3)=2x-3 | | 4x-2(x-4)=-7+4x+2 | | 23+3h=54 | | 268=215-y | | 1/5(-10a)= | | 9a-17b+15a= | | -0.7(3a)= | | 9x-(x-1)=17 | | 4p(np-z)=0 | | 0.89x+4=1.09x | | 7x+14=2x-36 | | -4x-2.5x+11+3.6x-16.4= | | 3x-11y-6x= | | 3(x-2)=-26-7x | | 7z-1=2(4z-3) | | (x+64)=(2x+39) | | 40+5x=5(7+2x) | | 3/4x-9=7 | | (3/2)x-163x | | -23=-9f-4f | | 2x+4y+2-y-9x-5= | | 4.75t+5=13.5t+12 |

Equations solver categories